Panchakarma's Synergistic Symphony: Harmonizing Health in Duchenne Muscular Dystrophy (DMD) (AYUSHDHARA, 2025)
Duchenne Muscular Dystrophy (DMD) is a rare genetic disorder characterized by progressive muscle degeneration. This article explores the Ayurvedic concept of Beeja dosha and its relevance to DMD management. By incorporating Panchakarma, a traditional Ayurvedic bio-purification protocol, into treatment plans, individuals with DMD may experience improved muscle strength, function, and overall quality of life. This study aims to deepen understanding of DMD from an Ayurvedic perspective, laying the groundwork for future research into Ayurvedic management strategies. A personalized and holistic approach to care, integrating Ayurvedic insights with conventional treatments, may offer new hope for individuals affected by this condition.